Cellular site and molecular mode of synapsin action in associative learning. - Michels, B.; Chen, Y.C.; Saumweber, T.; Mishra, D.; Tanimoto, H.; Schmid, B.; Engmann, O.; Gerber, B. (Learning and Memory, 2011)
Synapsin is an evolutionarily conserved, presynaptic vesicular phosphoprotein. Here, we ask where and how synapsin functions in associative behavioral plasticity. Upon loss or reduction of synapsin in a deletion mutant or via RNAi, respectively, Drosophila larvae are impaired in odor-sugar associative learning. Acute global expression of synapsin and local expression in only the mushroom body, a third-order "cortical" brain region, fully restores associative ability in the mutant. No rescue is found by synapsin expression in mushroom body input neurons or by expression excluding the mushroom bodies. On the molecular level, we find that a transgenically expressed synapsin with dysfunctional PKA-consensus sites cannot rescue the defect of the mutant in associative function, thus assigning synapsin as a behaviorally relevant effector of the AC-cAMP-PKA cascade. We therefore suggest that synapsin acts in associative memory trace formation in the mushroom bodies, as a downstream element of AC-cAMP-PKA signaling. These analyses provide a comprehensive chain of explanation from the molecular level to an associative behavioral change.